An exploratory study on moon-based observation coverage of sea ice from the geometry. Issue 16 (17th August 2020) - Liu, Huiying; Guo, Huadong; Liu, Guang; Ding, Yixing
ABSTRACT: Moon-based earth observation is an exploratory topic, expected to open up a new perspective on earth observation and has attracted considerable attention in recent years. Sea ice covers large areas of polar regions and plays a crucial role in the earth system. In this study, the moon-based observation coverage of sea ice is investigated in terms of geometric configuration. A simulation was carried out based on a simplified geometric model, the relative position of the moon to the earth, and the sea ice extent data. The results revealed both similarities and discrepancies between the moon-based observation coverage of Arctic and Antarctic sea ice. The main discrepancy was found in the better observation integrity of Antarctic sea ice. Moreover, the observation duration is longer and the observation coverage of sea ice is larger when the incidence angle is in the range of 20°–60° than in 20°–50°. With characteristics such as latitudinal imaging strip and continuous observation for several days in a sidereal month, the moon-based observation shows a large potential for monitoring Antarctic Marginal Ice Zone (MIZ). The peculiarities of moon-based observation may provide a new perspective for sea ice monitoring.